The Impact of Vitamin D Level on COVID-19 Infection: Systematic Review and Meta-Analysis - Teshome, Amare; Adane, Aynishet; Girma, Biruk; Mekonnen, Zeleke A. (Frontiers in Public Health, 2021)
Background: Coronavirus disease (COVID-19) is a respiratory and systemic disorder caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) or novel Coronavirus (nCoV). To date, there is no proven curative treatment for this virus; as a result, prevention remains to be the best strategy to combat coronavirus infection (COVID-19). Vitamin D deficiency (VDD) has been proposed to play a role in coronavirus infection (COVID-19). However, there is no conclusive evidence on its impact on COVID-19 infection. Therefore, the present review aimed to summarize the available evidence regarding the association between Vitamin D levels and the risk of COVID-19 infection. Methods: A systematic literature search of databases (PUBMED/MEDLINE, Cochrane/Wiley library, Scopus, and SciELO) were conducted from May 15, 2020, to December 20, 2020. Studies that assessed the effect of vitamin D level on COVID-19/SARS-2 infection were considered for the review. The qualities of the included studies were evaluated using the JBI tools. Meta-analysis with a random-effects model was conducted and odds ratio with their 95%CI were reported. This systematic review and meta-analysis are reported according to the preferred reporting items for systematic review and meta-analysis (PRISMA) guideline. Results: The electronic and supplementary searches for this review yielded 318 records from which, only 14 of them met the inclusion criteria. The qualitative synthesis indicated that vitamin D deficient individuals were at higher risk of COVID-19 infection as compared to vitamin D sufficient patients. The pooled analysis showed that individuals with Vitamin-D deficiency were 80% more likely to acquire COVID-19 infection as compared to those who have sufficient Vitamin D levels (OR = 1.80; 95%CI: 1.72, 1.88). Begg's test also revealed that there was no significant publication bias between the studies (P = 0.764). The subgroup analysis revealed that the risk of acquiring COVID-19 infection was relatively higher in the case-control study design (OR = 1.81). Conclusions: In conclusion, low serum 25 (OH) Vitamin-D level was significantly associated with a higher risk of COVID-19 infection. The limited currently available data suggest that sufficient Vitamin D level in serum is associated with a significantly decreased risk of COVID-19 infection.